Application of stretching techniques in physical rehabilitation of football players with traumas of upper and lower limbs - Doroshenko, E. Y. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to study and experimentally test effectiveness of application of stretching as auxiliary not specific component of complex rehabilitation of football players with traumas of limbs.